Physiological and Nutrient Responses to Nitrogen, Phosphorus, or Potassium Deficiency of Hydroponically Grown Strawberry - Wei Jiang; Jia Zhang; Zhi-Hang Jia; Ting Zhang; Wen-Jie Zhang; Meng Wei (HortScience, 2023)
Nutrient-depleted soil is a major constraint for crop production, particularly for fruits. Here, we investigated the different response of nitrogen (N), phosphorus (P), and potassium (K) deficiency on the growth and development of strawberry (Fragaria ×ananassa Duch.) in sand culture under greenhouse conditions. Compared with K, the lack of N or P is more unfavorable to strawberry growth and development. N deficiency affected shoot-root (S/R) ratio at different growth stages, and decreased the shoot biomass. P deficiency greatly increased the N content but decreased K content of the plants, which means P is of advantage to regulate the absorption and utilization of N and K nutrients in plants. Meanwhile, P has a profound influence on fruit quality, such as total soluble (TSS) sugar content. K deficiency is not conducive to fruit coloring and the formation of high-quality commercial fruits. The results contribute to a better understanding of the difference of N, P, or K deficiency on strawberry growth, nutrient absorption, and fruit quality during the whole growth period.